2022
DOI: 10.3390/ma15134563
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanical Properties of Concrete Using Basalt-Based Recycled Aggregate and Varying Curing Conditions

Abstract: To replace porous basalt, the mechanical properties of concrete with recycled resources and durability improvement were analyzed in this study. The analysis was based on the quality improvement of recycled aggregate, use of fly ash, and changes in curing conditions. Basalt aggregate (BA) with a 3% water absorption, raw recycled aggregate and basalt (RRA), and improved recycled aggregate and basalt (PRA) were the main experimental variables. As PRA was applied to concrete, the compressive strength was lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The study showed that incorporating fly ash can improve the late strength of steam-cured concrete, reduce crack sensitivity, enhance the resistance of steam-cured concrete to chloride ion penetration, and improve the durability of the concrete. Wu Kegang et al [ 15 , 16 , 17 , 18 , 19 ] investigated the impact of high-volume fly ash content on the porosity, including both the macro- and micropores, of steam-cured fly ash concrete. Their study revealed that, under steam-curing conditions, the porosity, including both large and small capillary pores, of steam-cured fly ash concrete was lower than that of standard-cured fly ash concrete when the fly ash content exceeded 40%.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that incorporating fly ash can improve the late strength of steam-cured concrete, reduce crack sensitivity, enhance the resistance of steam-cured concrete to chloride ion penetration, and improve the durability of the concrete. Wu Kegang et al [ 15 , 16 , 17 , 18 , 19 ] investigated the impact of high-volume fly ash content on the porosity, including both the macro- and micropores, of steam-cured fly ash concrete. Their study revealed that, under steam-curing conditions, the porosity, including both large and small capillary pores, of steam-cured fly ash concrete was lower than that of standard-cured fly ash concrete when the fly ash content exceeded 40%.…”
Section: Introductionmentioning
confidence: 99%